Ologen Implant versus Mitomycin C for Trabeculectomy: A Systematic Review and Meta-Analysis - Miao He; Wei Wang; Xiulan Zhang; Wenyong Huang (2014)
Objective To evaluate the application of the Ologen implant compared to mitomycin C (MMC) on the outcome of trabeculectomy and to examine the balance of risks and benefits. Methods A systematic literature search (Pubmed, Embase, the Cochrane Library, and the Chinese Biomedicine Database) was performed. Randomized controlled trials comparing the Ologen implant with MMC in trabeculectomy were selected. The efficacy measures were the weighted mean differences (WMDs) for the intraocular pressure reduction (IOPR), the reduction in glaucoma medications, and the relative risks (RRs) for success rates. The tolerability measures were RRs for adverse events. The pooled effects were calculated using the random-effects model. Results Seven randomized controlled trials including 227 eyes were included in this meta-analysis. The WMDs of the IOPR comparing the Ologen group with the MMC group were −2.98 (95% Cl: −5.07 to −0.89) at one month, −1.41 (−3.72 to 0.91) at three months, −1.69 (−3.68 to 0.30) at six months, −1.94 (−3.88 to 0.01) at 12 months, and 0.65 (−2.17 to 0.47) at 24 months. There was no statistically significance except at one and 12 months after surgery. No significant difference in the reduction in glaucoma medications or complete and qualified success rates were found. The rates of adverse events also did not differ significantly between Ologen and MMC. Conclusions The Ologen implant is comparable with MMC for trabeculectomy in IOP-lowering efficacy, reduction in the number of glaucoma medications, success rates, and tolerability. However, the results should be interpreted cautiously since relevant evidence is still limited, although it is accumulating. Further large-scale, well-designed randomized controlled trials are urgently needed.